Kombinasi Pupuk Kotoran Ayam dan Pupuk NPK Terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays saccharata Sturt) Pada Tanah Ultisol - Saputra, Agung; Irianto, Irianto; Antony, Dedy (Jurnal Media Pertanian, 2025)
This study aimed to examine the effect of combining chicken manure fertilizer and NPK fertilizers on the growth and yield of sweet corn (Zea mays saccharata Sturt) grown on Ultisol soil. The research was conducted in Pelawan Jaya Village, Sarolangun, Jambi, using a Randomized Block Design with eight combinations of chicken manure fertilizer doses (0–30 ton ha-1) and NPK (0–300 kg ha-1). Soil analysis showed that the Ultisol had acidic pH, low nitrogen and organic carbon content, high phosphorus, and low potassium levels. The chicken manure fertilizer used met the Indonesian National Standard (SNI) with good macro-nutrient content. The combined application of chicken manure fertilizer and NPK significantly improved vegetative growth parameters (plant height, leaf number, leaf area, stem diameter) and sweet corn yield components (ear weight, diameter, and length) compared to no fertilization. The optimal dose was 10 ton ha-1 chicken manure fertilizer combined with 200 kg ha-1 NPK, which produced the best growth and yield. Excessive chicken manure fertilizer without NPK did not optimally increase yield. Using chicken manure fertilizer can reduce the use of NPK by up to 50%.